#TITLE_ALTERNATIVE# - POETRA YOGA HADISOESENO (NIM. 18011018), NELSON
This thesis studies about contact resistance on copper conductor contact relative to plating materials, plating thickness, and contact pressure. This study is important because conductor contact plays an important role on electric distribution performance. A good conductor contact would have low contact resistance, low energy losses and better reliability. In this study, the sample that going to be tested are conductor contact without plating, conductor contact with zinc plating, conductor contact with nickel plating, and conductor contact with silver plating. First aspect that is going to be tested is contact resistance measurement without load on each. The next test is contact resistance and temperature measurement with DC load of 9, 18, and 27 A. Each test is conducted with the contact pressure variation of 5.6, 7.0, dan 8.4 MPa, and with plating thickness of 5, 15, and 25 μm. The result shows that conductor contact with 5 μm silver plating have much lower contact resistance and lower energy losses compared to all the other configuration.